Theoretical method for generating solitary waves using plunger-type wavemakers and its Smoothed Particle Hydrodynamics validation. (January 2021) - He, Ming; Khayyer, Abbas; Gao, Xifeng; Xu, Wanhai; Liu, Bijin
ABSTRACT: Although solitary wave generation using a piston-type wavemaker has been common, the method cannot be applied to all wave tanks because many of them have been or will be equipped with plunger-type wavemakers. How to use a plunger to generate solitary waves as good as those generated by a piston is an unsolved but practically significant problem. Herein, a theoretical method is proposed. New formulae for the precise descent of an arbitrary-geometry plunger are derived and constraints on the produced wave height are given. Taking wedge-shaped, box-shaped, and cylinder-shaped plungers as examples, the generic wave-making theory and constraints are then specified. On their bases a Smoothed Particle Hydrodynamics (SPH) model is applied to simulate the solitary wave generation, and its reliability is validated in advance by reproducing available experiments. The SPH-simulated wave profiles, velocity fields, and pressure fields are examined by comparing SPH results with analytical solutions. In addition, plunger-type and piston-type as well as Rayleigh-based and Boussinesq-based solitary wave generation are compared. The results show that the solitary wave generated by a plunger-type wavemaker can be as accurate as the one generated by a piston-type wavemaker, provided that the plunger does not have a sharp corner or an incompatible surface with the wave profile. It is therefore anticipated that the proposed theory will extend the functionalities of existing plunger-type wavemakers and benefit plunger design in the future.